Analysis of the efficacy and safety of a combined gemcitabine, oxaliplatin and pegaspargase regimen for NK/T-cell lymphoma - Wang, Jing-hua (Oncotarget, 2016)
Extranodal natural killer/T-cell lymphoma (ENKTL) is an aggressive neoplasm with a poor outcome. Novel L-asparaginase-based treatment regimens, such as GELOX (gemcitabine, oxaliplatin, and L-asparaginase) and P-gemox (gemcitabine, oxaliplatin, and pegaspargase), have shown promising results against stage IE/IIE ENKTL. To define the general applicability of P-gemox, in a retrospective analysis we examined the efficacy and safety of P-gemox in a cohort of 117 patients with newly diagnosed or relapsed/refractory ENKTL. Treatment included 2 to 8 cycles of P-gemox: intravenous gemcitabine (1250 mg/m(2)) and oxaliplatin (85 mg/m(2)) and intramuscular pegaspargase (2500 IU/m(2)) on day 1 and repeated every 2 weeks, or intravenous gemcitabine (1000 mg/m(2)) on days 1 and 8 and intravenous oxaliplatin (130 mg/m(2)) and intramuscular pegaspargase (2500 IU/m(2)) on day 1 and repeated every 3 weeks. Upon completion of treatment, the overall response rate was 88.8%, and responses were similar for newly diagnosed and relapsed/refractory patients. After a median follow-up of 17 months, the 3-year overall and progression-free survival rates were 72.7% and 57.8%, respectively. Multivariate analysis showed that CR after treatment was the most significant factor affecting survival. P-gemox thus appears to be an effective and well-tolerated treatment for patients with ENKTL.